The effect of teacher- and peer-assisted evaluative mediation on EFL learners’ metacognitive awareness development - Fathi, Sajjad; Shabani, Enayat A. (Englisia Journal, 2020)
Rooted in the heart of Vygotsky’s Sociocultural Theory, mediation has recently received considerable attention in the field of TEFL. The existing literature suggests that mediation can play an essential role in language learners’ performance development. In addition, learners need to know about their thinking process which is interpreted as metacognition.  This study aimed to investigate the effect of teacher- and peer-assisted evaluative mediation on learners’ metacognitive awareness development. To this end, 40 homogenized intermediate EFL learners were selected using a test of English language proficiency. The participants were then randomly divided into teacher-assisted (n=20) and peer-assisted (n=20) groups. Before the instructional phase, a metacognitive awareness questionnaire was given to the participants. At the instructional phase, the learners in the teacher-assisted group received teacher-assisted mediation. The learners in the peer-assisted group, however, were exposed to mediation provided by their peers. After the instructional phase, the metacognitive awareness questionnaire was given to the participants as the posttest of the study. SPSS was used to analyze the data. The descriptive statistics, the Shapiro-Wilk test of normality, and the Paired Sample T-test for inferential statistics were used to analyze the data. The findings showed that peer-assisted evaluative mediation had positive effects on developing students’ level of metacognitive awareness, whereas teacher-assisted evaluative mediation did not reveal such effects. It could be concluded that peer-assisted evaluative mediation is an effective tool for improving students’ metacognitive awareness.